Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1530/jme-17-0185
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone induces pro-angiogenic factors and assists homing of MSC into the cardiac tissue

Abstract: The use of mesenchymal stem cells (MSC) as a therapeutic tool in cardiovascular diseases is promising. Since androgens exert some beneficial actions on the cardiovascular system, we tested our hypothesis that this hormone could promote MSC-mediated repair processes, also. Cultured MSCs isolated from Wharton's jelly were exposed to 30 nM dihydrotestosterone (DHT) for 1 or 4 days and the effects of the hormone on their growth/migration/adhesion and the underlying mechanisms were assessed. Results were obtained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…One can safely assume that the increase in proteolytic activity is a precursor for the removal of damaged scar tissue. The data are consistent with the results of our previous experiments on human Wharton's Jelly-derived mesenchymal stromal cells (MSCs) [26], except that, in the present experiments, the DHT-induced increase in MMP-2 mRNA was not accompanied by enhanced protein expression in EPCs. It has been reported that the formation and activity of MMPs are controlled at several steps, such as genetic transcription and the conversion of latent enzymes into active forms; therefore, the lack of correlation between MMP-2 mRNA expression and protein levels is not an uncommon phenomenon [27].…”
Section: Discussionsupporting
confidence: 93%
“…One can safely assume that the increase in proteolytic activity is a precursor for the removal of damaged scar tissue. The data are consistent with the results of our previous experiments on human Wharton's Jelly-derived mesenchymal stromal cells (MSCs) [26], except that, in the present experiments, the DHT-induced increase in MMP-2 mRNA was not accompanied by enhanced protein expression in EPCs. It has been reported that the formation and activity of MMPs are controlled at several steps, such as genetic transcription and the conversion of latent enzymes into active forms; therefore, the lack of correlation between MMP-2 mRNA expression and protein levels is not an uncommon phenomenon [27].…”
Section: Discussionsupporting
confidence: 93%
“… [ 157 ] DHT Wharton’s jelly In vitro Increased proliferation; upregulated cell migration and pro-angiogenic factors, such as MMP-9, VEGF, and angiogenin. [ 156 ] Oxytocin Bone marrow (diabetic rat) Myocardial infarction In vitro / in vivo (rats) Restored secretion of KLF2; increased angiogenesis in vitro; improved cardiac function and reduced fibrosis in vivo. [ 159 ] Melatonin Bone marrow (rat) Osteoporosis and colitis model In vitro / in vivo (rats) Preserved self-renewal and differentiation capacity after long-term passaging; preserved therapeutic potential of long-term passaged MSC in bone regeneration and immunotherapy in vivo.…”
Section: Msc Priming With Other Moleculesmentioning
confidence: 99%
“…The hormone dihydrotestosterone (DHT) stimulates MSC proliferation, migration, and tissue engraftment. In addition, DHT-primed MSC contribute to cardiac regeneration [ 156 ]. Other studies have explored the effects of Apelin-13 peptide priming on MSC differentiation, proliferation, and survival in ischemic models.…”
Section: Msc Priming With Other Moleculesmentioning
confidence: 99%
“…Hormones also promote myocardial repair after infarction. Dihydrotestosterone induces angiogenic factors and helps to nest MSCs into heart tissue (92). Furthermore, irisin plays an anti-MI role by promoting angiogenesis (93).…”
Section: Application Of Angiogenesis For Cardiac Repairmentioning
confidence: 99%